If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + 3 = -21 Reorder the terms: 3 + h = -21 Solving 3 + h = -21 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + h = -21 + -3 Combine like terms: 3 + -3 = 0 0 + h = -21 + -3 h = -21 + -3 Combine like terms: -21 + -3 = -24 h = -24 Simplifying h = -24
| 12-4n=-18+11n | | 1/4(0)+4=y | | b-23=14 | | (1/2)x^2-x-7=0 | | y^2(9/2)=-3y | | -3n^3+4n^2-8n=-8 | | 60=6(n-8) | | -138=-20(v-985)-638 | | 5x+12-14=22 | | y^2(9/2)=-4 | | 3/-95+6=4 | | 1/4(0)+4 | | 6y+=8 | | 2y+12=18 | | -7+2n=4n+7 | | -5/7=r/14 | | x+50-8=-7 | | y/8=25 | | 699=-12(s-980)+75 | | 30x=30x | | 10x-25-3b=4b-1 | | -x^2-4x+3=-6 | | 2(-3/9)=(-3/9)2 | | 10z-5+3z=8-2z | | 6+1x=34 | | 45+15h=120 | | 5(6/7) | | ln(8x-1)=-5 | | 10(2m+10)+8=-6-2(5m-7) | | c=a+x/b | | 9(n+329)+146=146 | | 3(x-8)+6(x-12)=12 |